A Study on a Two-Way Post-Tensioned Concrete Waffle Slab. (2016) - Moldovan, Ilinca; Mathe, Aliz
Abstract: Post-tensioned construction has for a long period of time occupied a significant position, especially in the construction of bridges, storage tanks, but also in buildings. In this paper are presented the aspects of a square shaped waffle slab calculation, supported punctually and having a two-way post tensioning reinforcement disposed parabolically. It is described the waffle slab system, its characteristics, preliminary design of composing elements, technological aspects regarding the manufacturing of precast panels, details regarding used materials, the reinforcement layout and the calculation of prestressing force.